Using Comic Strips to Improve Reading Comprehension of Narrative Texts among Junior High School Students - Rapika Rismawati; Annie Susany Somantri (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
Reading comprehension is a fundamental skill for EFL learners, yet many students struggle to understand narrative texts due to limited vocabulary and difficulty analyzing textual structure. This study aimed to improve students’ reading comprehension through the use of comic strips as a learning medium. The research employed a classroom action research design with two cycles, each consisting of four meetings. The participants were 36 eighth-grade students of SMP Al-Hikmah Cipatat in the academic year 2024/2025. Data were collected through reading comprehension tests, observation checklists, questionnaires, and documentation. The results showed a steady improvement in students’ reading comprehension. The mean score increased from 58.61 in the pre-test to 68.19 in post-test I, and finally to 78.47 in post-test II, indicating that the mastery criterion was achieved by more than 75% of students. Observational data confirmed higher engagement and participation, while questionnaire responses revealed that students perceived comic strips as enjoyable and helpful in understanding narrative structure. In conclusion, the use of comic strips successfully enhanced students’ comprehension of narrative texts by combining visual and textual elements that facilitated both literal and inferential understanding. This study suggests that comic strips can serve as an effective and motivating medium in EFL classrooms.